(untitled) (Research, Society and Development, 2022)
The environmental impacts have increased in a disorderly way, as well as the irregular use of water due to the techniques used by the population that end up contributing to this problem, such as the use of artesian wells. This study was carried out in Serra Gravatá, located in the city of Jardim-CE, and addresses the main environmental and health impacts that the local community faces. The objective is to carry out a survey and identify the main environmental impacts present in the locality. Specifically, it is intended to verify the use and occupation of the soil in the region, the increase in the drilling of artesian wells as a form of supply and use in agriculture. The methodology was based on a questionnaire and field visit, obtaining didactic material through conversations with residents. The people were chosen at random among the families residing in the place. They cited deforestation, soil erosion, fires and visual pollution as the main environmental impacts.